IMPROVED MEASUREMENTS OF CROSS-SECTIONS AND ASYMMETRIES AT THE Z(0) RESONANCE - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; et al. (1994)
During the 1992 running period of the LEP e+e- collider, the DELPHI experiment accumulated approximately 24 pb-1 of data at the Z0 peak. The decays into hadrons and charged leptons have been analysed to give values for the cross sections and leptonic forward-backward asymmetries which are significantly improved with respect to those previously published by the DELPHI collaboration. Incorporating these new data, more precise values for the Z0 resonance parameters are obtained from model-independent fits. The results are interpreted within the framework of the Standard Model, yielding for the top quark mass mt = 157-48+36 (expt.) -20+19 (Higgs) GeV, and for the effective mixing angle sin2 θefflept = 0.2328 ± 0.0013(expt.)-0.0003+0.0001(Higgs), where (Higgs) represents the variation due to Higgs boson mass in the range 60 to 1000 GeV, with central value 300 GeV.